Modulation of Lignin and its Implications in Salt, Drought and Temperature Stress Tolerance - P.B., Kavi K.; B., Srinivas; Singam, Prashant; G., Sahitya; V., Tulya R. S.; G., Rajasheker; Suravajhala, Prashanth (Current Chemical Biology, 2023)
Background: Lignins are phenylpropanoid polymers with complex composition and structures and crucial components in plant cell walls. Lignins are biosynthesized from oxidative polymerization of 4-hydroxycinnamyl alcohols, but differ in the degree of methoxylation. Objective: This review makes an endeavour to identify the gaps in our understanding of lignin modulation and gain insights into their relevance to abiotic stress tolerance. Methods: Critical review of the recent literature to understand the regulation of lignin, the major biopolymer involved in a multitude of functions. Results: Lignin contributes to the growth of tissues, and organs that give mechanical protection or lodging resistance and also responds to multiple biotic and abiotic stresses. The quantity and quality of accumulation of lignin is dependent on the type of plant species and abiotic stress. In this review, we briefly discuss the biosynthesis, modulation of lignin by diverse transcription factors and its role in salt, drought and temperature stress tolerance. Conclusion: We need to explore many areas to gain comprehensive knowledge about the secondary cell wall deposition of monolignols, and their transport, leading to lignin accumulation which imparts biotic and abiotic stress tolerance to plants.
Keywords: monolignol deposition